Gas Turbine Tubular Coilpipes Regenerators Optimized According to the Minimum Mass Criterion - Gorbov V. M.; Movchan S. N.; Solomonyuk D. N. (Problems of the Regional Energetics, 2021)
The aim of this work is to determine the effect of the elements, which do not participate in heat transfer, on the mass of the regenerator of a gas turbine plant X, as well as to define the re-strictions that are imposed on the regenerator design based on the conditions of manufacturabil-ity, placement at the facility and transportability. This goal is achieved using an algorithm for finding rational geometric parameters of the heat exchange matrix with minimization of the re-generator mass by Newton's method. It has been determined that the mass of the heat exchange matrix can be 0.48–0.58 of the mass of the regenerator. This makes it necessary, even at the initial design stages, to take into account the effect of the above factors on the mass of the re-generator and the choice of the rational geometrical parameters. A significant result of the stud-ies performed is determination of the effect of dimensional restrictions and requirements for the shape of the regenerator to be increased in its mass. The values of the geometrical parameters of the heat exchange matrix were obtained, at which the mass of the regenerator takes on a mini-mum value. The significance of the work is that the obtained relationships between the mass of the regenerator and its geometry makes it possible to reduce the metal consumption of the regen-erator and the gas turbine plant, which allows designing the heat exchangers for power plants.